The past, present, and future of cross-border cooperation between municipalities in the South Bohemian region: A case study - Jiří Dušek (Administrative Sciences, 2024)
The aim of this study is to provide a comprehensive view of matters of cross-border cooperation, with the main emphasis on the typology and development of structures supporting cross-border cooperation in a selected region of the Czech Republic (South Bohemian Region). The study focuses on the analysis of changes in the methods and ways of cooperation of municipalities in the programming periods 2007-2013 and 2014-2020 (Euroregions, cross-border impulse centers, European territorial cooperation groups, partner and friendly cities, etc.). The research not only analyzes the actual development of cooperation between municipalities in the region studied, but also identifies the prerequisites of and barriers to cross-border cooperation. The data obtained show a significant decrease in the interest of municipalities in cross-border cooperation within the conditions of the Czech Republic in recent years. The current situation with regard to the existence and development of cross-border cooperation in 2024 is not very satisfactory, although it is paradoxically an area strongly supported by the EU Cohesion Policy. This study employs a mixed-methods approach, combining both qualitative and quantitative research methods to provide a comprehensive analysis of cross-border cooperation in the South Bohemian Region. A thorough review of existing literature on cross-border cooperation and related policies was conducted to establish a theoretical framework. The practical part of the study is based on field research carried out by the author in 2007-2013 and 2014-2020. This research examined the level of cooperation between the 623 municipalities in the South Bohemian Region (in 2016, there were 624 municipalities in the region). In the case of cross-border impulse centers, the input data were represented by e-mail and telephone inquiries to representatives of individual municipalities and the websites of Euroregions. To conduct a comprehensive study on cross-border cooperation between municipalities in the South Bohemian Region, logical and scientific methods were used. Universal methods of logic ensured the correctness and orderliness of the thought process, with abstraction identifying key elements. Synthesis was used to divide the study into parts, analyze them in detail, and integrate them into a comprehensive analysis. Scientific methods included analysis to examine the current status and frameworks of cross-border cooperation and comparison to identify similarities or differences between the Czech Republic and neighboring countries.
Keywords: 350; cross-border cooperation; Czech Republic; municipality; region; regional development